(untitled) (Revista de Ciências Agroveterinárias, 2004)
The experiment was carried out during the winter and spring crop seasons of 2000, in a plastic greenhouse at the department of plant production, federal university of Santa Maria. The purpose of the experiment was to evaluate the growth of lettuce cultivated in different substrates. The treatments were humus + raw rice husk (H+RRH), comercial substrate (CS), humus (H), raw rice husk (RRH), carbonized rice husk (CRH), and peat (P). Fertirrigation was provided based on the atmospheric necessities, with nutrient solution. The experiment followed a completely randomized design with four replicates. The experiment was finished when one of the treatments achieved 200g of green mass. The evaluated parameters were shoot fresh and dry matter and leaf area of the plants. The treatments H, CS and H+RRH, with shoot fresh matter of 318g, 280.5g and 223.5g, respectively, obtained the minimum green mass stipulated on the same period of cultivation for the studied seasons.